Fintech Peer to Peer Lending: Determinan dari Intensi Penggunaan Kembali - Kusumawati, Ratna Dewi; Simatupang, Apriani; Mahsun; Muamilah, Husnul; Rahmatika, Tia (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study was conducted with carefully to show the result of the influence of some selected factors to the intention to reuse P2P lending by former borrowers. The selected factors are trust, ubiquity, and perceived usefulness. The background of this study is due to phenomenon of the drastic decline of P2P lending platform providers in recent years. The amount of data collected and can be processed through the distribution of questionnaires to the respondent is 123. The results show that ubiquity and perceived usefulness variable significantly affect intention to reuse P2P lending variable, but trust has no significant influence to the intention to reuse P2P lending. The rest, the F test conducted indicate that the variables of trust, ubiquity, and perceived usefulness simultaneously affect intention to reuse P2P lending.